The Dilemma of Particular Ethics: an Analysis of The Rejection of Israeli Athletes at A Gymnastics Tournament in Indonesia - Luis Fernandez, Aloysius Don; Puspitasari, Maria; Badry, Ahmad Ibrahim (Journal Research of Social Science, Economics, and Management, 2026)
The rejection of Israeli athletes’ participation in several international sporting events held in Indonesia has given rise to a complex ethical debate between the universal principles of international sport and the particular values embraced by the Indonesian nation. This study aims to analyze the particular ethical dimensions in the policy of rejecting Israeli athletes from international gymnastics tournaments in Indonesia and its implications for national resilience. The study uses a qualitative approach with a case study design through the analysis of documents, policies, media reports, and academic literature on sports ethics, deontology, Olympism, and national resilience. The results show that the policy of rejecting Israeli athletes cannot be understood solely as a discriminatory act in sport but rather as a manifestation of particular ethics rooted in constitutional values, humanitarian solidarity with Palestine, and Indonesia’s foreign policy orientation. However, the policy creates tension with the universal principles of international sport, which emphasize non-discrimination, political neutrality, and equal participation of athletes. The research findings indicate that this dilemma reflects a struggle between domestic moral legitimacy and global normative legitimacy. From a national resilience perspective, this case demonstrates the importance of maintaining a balance between the nation’s moral identity, humanitarian commitment, and the demands of international sporting governance. This research confirms that moral resilience at the national level is an important factor in facing increasingly complex global dynamics.